Who is the “Student”? A Critical Analysis of Neoliberal Education Reform Legislation - Janzen, Melanie; Heringer, Rebeca (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Neo-liberal reforms in education have been sweeping the globe, undermining education as a public good, and diminishing its contributions to democratic life. Using post-structural perspectives, this article provides a critical discourse analysis of a proposed legislative bill in the province of Manitoba, Canada, as it relates to the construction of the “student.” Using Foucault’s conceptualizations of governmentality and historical ontology of the subject, we interrogate the government’s proposed Bill 64 in order to reveal how policy works to constitute particular subjects. Our analysis reveals that Bill 64 constructs the student—through its relations to knowledge, others, and the self—as objectified and homogenous, and as being valued for economic contributions, thereby marginalizing other ways of being. By revealing the oppressive effects of neo-liberal discourses on students’ subjectivities, this article aims to inform educators, education researchers, and policy makers in the pursuit of more equitable educational policies and systems.